A giant lumbar chordoma: A case report. Issue 25 (June 2018) - Zhou, Yibiao; Hu, Bolin; Wu, Zhiwei; Cheng, Hanxiong; Dai, Min; Zhang, Bin
Abstract: Rationale: Chordomas are malignant neoplasms derived from incomplete regression of notochordal tissue along the craniococcygeal axis.It is rare for Chordoma arising from the lumbar spine and the traditional long-term prognosis is typically poor. Patient concerns: The persistent pain in the left side of the waist about 2 years. Diagnoses: Chordoma. Interventions: The patient was treated with surgical resection of the total tumor, followed by the spinal internal fixation of L1 to L2 with pedicle screws. Outcomes: After 5 month follow-up, we find the recurrence in the original lesion.At the 15 month follow-up, the patient was dead after a lot of times revisit by various doctor. Lessons: So It is suggest that the diagnosis should be carried out accurately at the early stage, the lesions and source of lesions should be cut away as broadly as possible, also the radiation and chemotherapy should be carried out after the operation as necessary.